Machiavelli and the rise of political realism - Nemenzo, Francisco 1935- (U.P. Diliman Interactive Learning Center, 2005)
The fourth of a series of lectures under the project Exploring the Technology of Videoconferencing in Teaching Social Science II: a general education course on the social, economic and political thought.